Peran Sarana dan Prasarana dalam Meningkatkan Kualitas Pendidikan Islam: The Role of Facilities and Infrastructure in Enhancing the Quality of Islamic Education - Abdul Jabar Idharudin; Muwahidah Nurhasanah; Budi Heriyanto (DIRASAH: Jurnal Kajian Islam, 2025)
This study aims to describe the availability, utilization, and impact of facilities and infrastructure on the implementation of Islamic education at SDIT Al-Hidayah Bogor. The research employs a descriptive qualitative approach, utilizing data collection techniques that include observation, interviews, and documentation. The results show that SDIT Al-Hidayah Bogor possesses adequate facilities and infrastructure that align with the needs of integrated Islamic-based learning, including classrooms, prayer rooms, laboratories, libraries, and supporting areas. These facilities are optimally utilized to support teaching and learning activities as well as the development of students' Islamic character. The presence and quality of the facilities play a significant role in creating a conducive, efficient, and religious learning atmosphere. The findings imply that good facilities and infrastructure are key factors in the success of integrated Islamic education.